Early educational attainment in children with major congenital anomaly in the UK - Wands, Zoë E; Cave, Daniel G W; Cromie, Kirsten; Hough, Amy; Johnson, Kathryn; Mon-Williams, Mark; Feltbower, Richard G; Glaser, Adam W (Archives of disease in childhood, 2024)
ObjectiveTo describe early educational attainment and special educational needs (SEN) provision in children with major congenital anomaly (CA) compared with peers.DesignAnalysis of educational data linked to the ongoing Born in Bradford cohort study. Confounders were identified via causal inference methods and multivariable logistic regression performed.SettingChildren born in Bradford Royal Infirmary (BRI), West Yorkshire.PatientsAll women planning to give birth at BRI and attending antenatal clinic from March 2007 to December 2010 were eligible. 12 453 women with 13 776 pregnancies (>80% of those attending) were recruited. Records of 555 children with major CA and 11 188 without were linked to primary education records.OutcomesKey Stage 1 (KS1) attainment at age 6–7 years in Maths, Reading, Writing and Science. SEN provision from age 4 to 7 years.Results41% of children with major CA received SEN provision (compared with 14% without), and 48% performed below expected standards in at least one KS1 domain (compared with 29% without). The adjusted odds of children with CA receiving SEN provision and failing to achieve the expected standard at KS1 were, respectively, 4.30 (95% CI 3.49 to 5.31) and 3.06 (95% CI 2.47 to 3.79) times greater than their peers. Those with genetic, heart, neurological, urinary, gastrointestinal and limb anomalies had significantly poorer academic achievement.ConclusionsThese novel results demonstrate that poor educational attainment extends to children with urinary, limb and gastrointestinal CAs. We demonstrate the need for collaboration between health and education services to assess and support children with major CA, so every CA survivor can maximise their potential.